(untitled) (Journal of the College of Basic Education, 2026)
This research examines and analyzes the dialectic between "ontological authority" and "legislative authority" in Twelver Shi’a thought, and their impact on the formulation of governance theories during the Major Occultation. The research begins with the premise that the two authorities are inseparable in the person of the infallible Imam (peace be upon him), where ontological authority (control over the universe and divinely inspired knowledge) is a prerequisite for exercising legislative authority (governance and legislation) in its absolute form. The research explores the conceptual essence of both authorities, clarifying that the Imam (peace be upon him) is the conduit of divine grace and the axis around which existence revolves, and that his occultation does not imply the suspension of this ontological role. It then proceeds to analyze the ontological hierarchy of the Imamate, explaining that the spiritual function (guidance) is the foundation, and temporal authority is a branch. on the practical side, the research discussed how this dialectic was embodied in the theories of "public representation" and "guardianship of the jurist," where the legislative function (administration of the state) was transferred to the jurists as a necessary measure to fill the void, while the formative and spiritual dimension remained the domain of the Hidden Imam, exercised through guidance and patronage. The research concluded that the Shiite political system during the Occultation is a "representative" system that derives its legitimacy from the unseen (the Imam) and its effectiveness from reality (the jurist and the community), awaiting the establishment of a divinely ordained state of justice.